2022
DOI: 10.1186/s12870-022-03465-4
|View full text |Cite
|
Sign up to set email alerts
|

The complete chloroplast genome of Onobrychis gaubae (Fabaceae-Papilionoideae): comparative analysis with related IR-lacking clade species

Abstract: Background Plastome (Plastid genome) sequences provide valuable markers for surveying evolutionary relationships and population genetics of plant species. Papilionoideae (papilionoids) has different nucleotide and structural variations in plastomes, which makes it an ideal model for genome evolution studies. Therefore, by sequencing the complete chloroplast genome of Onobrychis gaubae in this study, the characteristics and evolutionary patterns of plastome variations in IR-loss clade were compa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 90 publications
3
23
1
Order By: Relevance
“…Our results indicated that chloroplast genes clpP , rbcL , and ccsA were subjected to positive selection, indicating that they may have contributed to environmental adaptation in Ficus . The clpP gene, which encodes clpP protease, is also positively selected in several angiosperm lineages, such as Paphiopedilum (Orchidaceae) ( Guo et al, 2021 ), Acacia (Fabaceae) ( Dugas et al, 2015 ), and Bupleurum (Apiaceae) ( Huang et al, 2021b ), and shows hypervariability in Amaryllidaceae and Papilionoideae ( Liu et al, 2022 ; Moghaddam et al, 2022 ), suggesting it may have accelerated substitution rates in many angiosperms. Functional studies have also indicated that clpP protease degrades or restores damaged proteins ( Wicke et al, 2011 ), and is important for changes in plant development in response to stress ( Erixon and Oxelman, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that chloroplast genes clpP , rbcL , and ccsA were subjected to positive selection, indicating that they may have contributed to environmental adaptation in Ficus . The clpP gene, which encodes clpP protease, is also positively selected in several angiosperm lineages, such as Paphiopedilum (Orchidaceae) ( Guo et al, 2021 ), Acacia (Fabaceae) ( Dugas et al, 2015 ), and Bupleurum (Apiaceae) ( Huang et al, 2021b ), and shows hypervariability in Amaryllidaceae and Papilionoideae ( Liu et al, 2022 ; Moghaddam et al, 2022 ), suggesting it may have accelerated substitution rates in many angiosperms. Functional studies have also indicated that clpP protease degrades or restores damaged proteins ( Wicke et al, 2011 ), and is important for changes in plant development in response to stress ( Erixon and Oxelman, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the gene is either transferred to the nuclear genome, or its function is replaced by a nuclear gene ( Wang et al, 2018 ). Recent sequencing and analyses of some IRLC plastomes ( Kim et al, 2005 ; Li et al, 2018 ; Moghaddam et al, 2022 ) have revealed important evolutionary patterns in this clade, including loss of the genes rpl22 and rps16 , the deletion of one intron of clpP ( Jansen et al, 2008 ; Li et al, 2020 ), multiple sequence inversions ( Schwarz et al, 2015 ; Williams et al, 2015 ), and gene transfers to the nucleus ( Moghaddam and Kazempour-Osaloo, 2020 ; Wu et al, 2021 ). Vicia bungei plastome lacked one intron of clpP , which was consistent with the finding of Jansen et al (2008) and confirmed the parallel loss of this clpP intron in V. bungei and in members of the papilionoid IRLC.…”
Section: Discussionmentioning
confidence: 99%
“…Some Fabaceae plastomes have been highly rearranged owing to multiple rounds of translocations and/or inversions. As a result, the plastomes of the IRLC have undergone considerable diversification in both gene order and gene/intron content ( Wang et al, 2018 ; Li et al, 2020 ; Xin and Yang, 2020 ; Moghaddam et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…seed plants) exhibit a higher degree of conservation with respect to their gene content, structure and organization (Asaf et al, 2017). Most cpDNAs encode about 80 protein-coding genes that are primarily involved in photosynthesis and other biochemical processes, along with 4 rRNA and 30 tRNA genes (Moghaddam et al, 2022). A plant cpDNA typically has a circular structure and includes a large single-copy region (LSC), a small single-copy region (SSC) and two inverted repeats (denoted as IR1 and IR2) separating the LSC and SSC.…”
Section: Introductionmentioning
confidence: 99%